Political Public Relations: origins, challenges and applications - Gonçalves, Gisela Marques Pereira (2016)
When compared to corporate public relations, political public relations are still a new field of study, which nonetheless has a great development potential. This article presents a reflec-tion on public relations in the political sphere, by remembering its conceptual grassroots and studying the challenges imposed on its practice by the new media. Grounded in the relationship management theory and in the ideal of symmetrical and dialogic communication, this article, presents possible paths for applied research in the field of political public relations.